Proposição de um modelo de diagnóstico de competências por tipologia de projetos baseado na taxonomia de Bloom - Rosamilha, Nelson José (2023)
Organizations are undergoing several transformations due to the volatility of the economy, competition and the fourth industrial revolution. Faced with these challenges, in order to adapt, organizations need to restructure their production chains and establish organizational rearrangements and, thus, become more competitive. In this context, one of the critical success factors is the development of skills to improve and execute these activities, as well as the greater adoption of project management practices to demonstrate a clear delivery of products and services through projects. Despite the challenges and the scenario presented, project management professionals are dealing with increasingly complex projects, demanding from these professionals a group of increasingly extensive and specific skills. In addition, it is necessary to differentiate the types of projects according to their complexity, context and business approach. Based on the aforementioned elements, this thesis aimed to propose a model for diagnosing the competences of design professionals related to the design typology. To achieve the objective of this thesis, the research process was conducted through three studies, the first being a systematic review of the literature that sought to identify the competences of project professionals through the typology of the project. This study identified 170 competences distributed in 14 different project typologies, some of these competences with greater relevance for a given project typology. The second study aimed to propose a model for diagnosing competencies by project typology. Therefore, an exploratory-descriptive study developed in three stages was adopted for this purpose. In the first stage, a systematic literature review was applied, which was followed by a second stage of searches in the gray literature and, in the third stage, a search in public domain patents. As a result, after analyzing the corpus made up of the three stages, it was possible to propose a model for diagnosing competencies by project typology applying Bloom´s Taxonomy. As a result of this model, in study 3, an instrument for diagnosing competencies by project typology was created, which was applied in a field study and case study to diagnose the competencies of project professionals by project typology. As a practical result of the research, a request for registration of an invention patent was generated, resulting from the proposed model of this thesis with the responsible body in Brazil - INPI (National Institute of Industrial Property), as well as the registration of a computer program at INPI. Theoretical contributions can be evidenced in the advances in relation to the discussions on the specific adoption of competences by project typology in organizations, since for many researchers this list is generic and non-specific. In this same sense, the present thesis advances in the theoretical contribution by using Bloom's taxonomy to perform the diagnosis of competences of project professionals according to the specificities of each typology, qualifying these competences. This research is aligned with research line 2 “Project Management”, linked to the Graduate Program in Project Management – PPGP UNINOVE. This thesis is also in line with other research by his advisors linked to the project-axes "People Management and Project Management" and "Agile and Hybrid Projects"